THE INFLUENCE OF CUSTOMER VALUES ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY WITH THE MODERATION EFFECT OF CAFE ATMOSPHERE IN LHOKSEUMAWE CITY - Iskandarsyah; Sapna Biby; Ikramuddin; Jullimursyida; Nurainun; Heriyana (RADJA PUBLIKA, 2026)
The purpose of this study is to examine the influence of customer value on customer satisfaction and its impact on customer loyalty with the moderating effect of cafe atmosphere in Lhokseumawe City. The data in this study were 120 employees who responded to a questionnaire distributed through Google Form. The data analysis tool used Structural Equation Modeling (SEM) operated with Amos. The results of the study found that customer value significantly influenced job satisfaction and customer loyalty. Customer satisfaction also significantly increased customer loyalty. And in testing the mediation effect of customer satisfaction significantly mediated the influence of customer value on customer loyalty. Furthermore, in testing the moderation effect, cafe atmosphere significantly moderated the influence of customer satisfaction on customer loyalty. The results of this study are expected to provide important contributions for stakeholders in developing cafe business marketing strategies in the future.